2021
DOI: 10.1021/acs.nanolett.0c04242
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric Response of Antiferromagnetic CrI3 Bilayers

Abstract: We predict that layer antiferromagnetic bilayers formed from van der Waals (vdW) materials with weak interlayer versus intralayer exchange coupling have strong magnetoelectric response that can be detected in dual-gated devices where internal displacement fields and carrier densities can be varied independently. We illustrate this strong temperature-dependent magnetoelectric response in bilayer CrI3 at charge neutrality by calculating the gate voltage-dependent total magnetization through Monte Carlo simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…The Te(pz)-Fe(dz2) bond states occupation and splitting play a critical role in modulating MAE 1774 . Using MC simulations and mean-field solutions, Lei et al predicted that vdW AFM bilayers with weak interlayer and strong intralyer FM coupling possess strong magnetoelectric response, which can be detected in dualgated devices 1775 . Moreover, electric field can also induce halfmetallicity in magnetic vdW CrI3/CrGeTe3 heterostructures by electric-controlled band alignment in the asymmetric band structures 1776 .…”
Section: External Field Modulationmentioning
confidence: 99%
“…The Te(pz)-Fe(dz2) bond states occupation and splitting play a critical role in modulating MAE 1774 . Using MC simulations and mean-field solutions, Lei et al predicted that vdW AFM bilayers with weak interlayer and strong intralyer FM coupling possess strong magnetoelectric response, which can be detected in dualgated devices 1775 . Moreover, electric field can also induce halfmetallicity in magnetic vdW CrI3/CrGeTe3 heterostructures by electric-controlled band alignment in the asymmetric band structures 1776 .…”
Section: External Field Modulationmentioning
confidence: 99%
“…The asymmetry of electron and hole doping for the magnetic transition is consistent with the trend of a recent ab-initio calculation for the isolated CrI 3 bilayer [22], confirming it is an intrinsic feature of the bilayer. The asymmetry or lack of magnetic transition with hole doping, however, is an intriguing feature, as it is contrary to the general expectation that weak doping favors ferromagnetism [30], and also because some (but not all [22]) theoretical studies indicated a symmetric behavior [26,27]. The symmetry in the latter studies might be related to neglect of relativistic effects, but the factors controlling the asymmetry in the magnetic behavior have not been investigated so far.…”
Section: Introductionmentioning
confidence: 89%
“…In recent experiments, this spin-flip field could be tuned by several techniques, including in-plane strain [17], hydrostatic pressure [18,19], and electrostatic gating [15,16], while an irreversible AFM to FM transition was observed at high hydrostatic pressure (above 1.7 GPa) [18,19]. Theoretically, the exchange coupling was also shown to be sensitive to perturbations such as strain [20], change in layer stacking [21][22][23], electric field [24,25], electrostatic doping [22,26,27], and by coupling to other 2D materials [28] -in most cases with auspicious trends for FM transitions [20][21][22][23][24][25][26][27][28]. Each of the external perturbations acts through a different mechanism, offering much-needed versatility for diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for the interlayer exchange coupling, DFT calculations predict AFM coupling while the ground state is FM for Cr 2 Si 2 Te 6 [456], which may be due to the dipole-dipole interaction which is missing in most DFT calculations which can be considered by including the Breit correction [457]. Note that the interlayer exchange coupling is very sensitive to the distance, stacking, gating, and probably twisting [458], which can be used to engineer the spin Hamiltonian which should be evaluated quantitatively. Furthermore, as most of the 2D magnets have the honeycomb lattice with edge-sharing octahedra like the layered Na 2 IrO 3 and α-RuCl 3 which are both good candidates to realize the quantum spin liquid states [459], the Kitaev physics becomes relevant, e.g.…”
Section: Two-dimensional Magnetic Materialsmentioning
confidence: 99%